Traffic Operation Management Information System Using Extreme Programming Method - Ahmad Rizki; Dini Harisah; Muhammad Farid Azmi Aziz; Puji Rahayu (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
The Indonesian National Police (Polri) is a state instrument whose role is to maintain public security and order, enforce the law, and provide protection, protection and service to the community. To support this role, the Police carry out various kinds of police operations. One of them is on the traffic function, namely by carrying out traffic operations. The Traffic Police under the auspices of the Korlantas Polri is a state instrument that is responsible for police functions in the traffic sector. Having a large organization, with 34 Polda and 504 Polres throughout Indonesia, is a challenge for the Polri, especially the Korlantas Polri, in carrying out traffic operations. The challenge faced is that the process of making reports on the results of traffic operations takes a long time, because the activities of reporting, collecting and managing traffic operation data are still carried out in a simple manner. This study aims to build a web-based application that can assist the process of reporting, collecting and managing data from traffic operations, as well as processing it into useful information. This application development applies the Extreme Programming (XP) software development methodology. The choice of the XP method is because XP is one of the methodologies that supports the acceleration of the development of a system with a minimum number of teams. In addition, based on the results of the study, it was found that the implementation of the XP method in application development resulted in software that was in accordance with the requirements.